Factors that affect the occurrence of fumonisin. - Miller, J D (2001)
The two important Fusarium ear rots of corn, Gibberella ear rot (Fusarium graminearum, formally F. moniliforme and allied species) and Fusarium ear rot (F. verticillioides and allied species) grow under different environmental conditions. F. graminearum grows well only between 26 and 28 degrees C and requires rain both at silking and during disease progression. F. verticillioides grows well at higher temperatures, and ear rot and fumonisin accumulation are associated with drought and insect stress and growing hybrids outside their areas of adaptation. In southern Transkei, where esophageal cancer has been associated with the consumption of F. verticillioides and fumonisin-contaminated corn, environmental conditions favor this fungus in most years. In the nearby areas where the soils, crops, food consumption, and populations are the same and where esophageal cancer is low, temperatures are cooler and F. graminearum is favored. Although F. verticillioides is associated with a disease of corn, it may be that this fungus is a mutualistic endophyte of the plant. Perhaps because of this, breeding for resistance to Fusarium ear rot has produced inconclusive results to date. The best available strategies for reducing the risk of fumonisin contents of maize are to ensure that hybrids are adapted to the environment and to limit drought stress and insect herbivory. It may also be necessary to make use of alternative strategies such as producing hybrids that contain enzymes to degrade fumonisin as it is produced.